Analisis Skrining Tuberkulosis Anak melalui MT (Mauntox Test) Terhadap Status Gizi Balita - Indria Nuraini; reni umbarawati; Retno Setyo Iswati; Nurul Farida (Wahana : Tridarma Perguruan Tinggi, 2024)
The Tuberculin Skin Test (TST) is a relevant tuberculosis diagnostic test, with sensitivity and specificity ≥ 90%. Nutritional status is an important factor in the occurrence of infectious diseases, including TB. Nutritional status greatly determines the body's ability to fight TB germs. Children with good nutrition can prevent the spread of the disease, while children with poor nutritional status or stunting can cause lung disease with large cavities at an early age. This research aims to determine Child Tuberculosis Screening via MT (Mauntox Test) on the Nutritional Status of Toddlers. The population of this study were toddlers aged 1-59 months with stunting. The stages of this research include: Scoring system, namely weighting symptoms or clinical signs in children suspected of having TB by carrying out anamnesis and physical examination (Symptom scoring and TB supporting examinations), Determining Status Toddler nutrition is measured anthropometrically based on height for age (TB/U) and (WW/U) with Z-Score, Tuberculin Test. Test data analysis using Logistic Regression, to see the level of influence of Tuberculosis Screening via the Mountox Test on the incidence of Stunting, while bivariate testing using chi square and multivariate testing using Logistic Regression. Research results: age, gender, immunization status and the results of the Mauntox screening test did not affect the nutritional status of toddlers, whether based on PB/U or BB/U because it was seen that the p-value was >0.10. Meanwhile, gender has a 1,258 times risk of stunting (PB/U) and age has a 2,054 times risk of very poor nutritional status (BB/U). The conclusion is that there is no effect of the Mauntox test on the nutritional status of toddlers